An exploration of the use of technology by congregations - S. Joubert; W. J. Schoeman (Acta Theologica)
The internet, cell phones and, more broadly speaking, the social media, have changed the world over the past twenty years, resulting in what is called “the network society”. What is the response of South African congregations to the use and role of technology in congregational life? The aim is to provide an empirical and theoretical description of the situation in this regard. An empirical survey was conducted among congregations in the eastern suburbs in Pretoria and the northern suburbs of Cape Town and it was found that congregations communicate mostly information through the social media. Congregations that function within a fluid network society should earnestly consider devising a proper and effective digital and electronic communication strategy for the congregational ministry. Congregations that wish to remain relevant within the aetas digitalis must undergo a shift from being mere providers of the correct information, to becoming mentors, co-travellers and wise guides who assist one another, as well as others, to make sense of this information in order to apply it, to the glory of God and for the benefit of others.